A Servey on the effects of foreign investment in west Malaysia / Li Howe Seng - Li, Howe Seng (1974)
The coming of the foreign investors to Malaysia is largely influenced by the historical factors in the past. Prior to independence, the Portuguese, the Dutch and later the British came to conquer Malaya. Malaya being under the administration of the colonialists, was left with an economy which was shaped to serve their own interests. Not only was the economy of this country dependent and influenced by them, we also find that our political and social institutions were under their domination and influence. Although Malaya was not under the administration of the United States, but they have come here to dominate the economy. Whether the Western powers came as colonialists or economic exploiters, they are still under the name of imperialism. The substance of imperialism is essentially economic exploitation of other people buttressed by political and military domination.